Ornamental Variety Assessment of Different Indramayu Batik through Accessing Universal Value (OUV) and Geographical Indications (GI) - Maiyang, F.; Taqyuddin (Recent Research Advances in Arts and Social Studies Vol. 3, 2023)
This chapter develop an assessment of Indramayu batik based on Outstanding Universal Value (OUV) and Geographical Indications (GI). OUV has three types of criteria, namely basic criteria for cultural products, integrity criteria, and product authenticity criteria. To fulfill GI, Indramayu batik needs to be able to explain the name of the GI being applied, the name of the item, its characteristics, geographical environment, coverage area, history and traditions contained, production processes, quality test methods, and labels for Indramayu batik. Batik is an Indonesian cultural heritage that has been known since the early 19th century until now. Batik art in each region can be seen from the manufacturing process, batik quality, ornament, and color arrangement. This study discusses which ornaments of Indramayu batik represent the production area the most, then Indramayu batik is assessed on two grounds, namely Outstanding Universal Value (OUV) and Geographical Indication (GI). Additionally, the finding of this study revealed that spatial patterns formed from the results of the assessment of Indramayu batik based on OUV and GI. The qualitative approach was adopted to develop the study in which the data was collected through interviews. Indramayu batik business owners and Indramayu batik craftsmen from 22 different locations of Indramayu batik producers was participated in the interviews. Analysis of the collected data carried out by applying two approached including descriptive analysis and spatial analysis. The results of this study are sekar niem and kapal kandas ornaments get the highest value based on OUV and GI, while merak berunding, liris, parang teja, and banji are the ornaments with the lowest value. The similarity of these ornaments is to get influence from Cirebon. While merak berunding, liris, parang teja, and banji are ornaments with the lowest value based on GI and OUV. These ornaments have similarities with each other, namely describing the values held by the local community.